2014
DOI: 10.1039/c4py00609g
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of microporous polymers using Tröger's base formation

Abstract: A step-growth polymerisation based on the formation of Tröger's base, performed by simple reaction of a suitable aromatic diamine monomer with dimethoxymethane in trifluoroacetic acid, provides polymers of high average molecular mass. The properties of the resulting polymers can be tailored by the choice of monomer. In particular, the Tröger's base polymerisation is highly suited to the preparation of soluble polymers of intrinsic microporosity (PIMs) due to the resulting fused-ring TB linking group, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 50 publications
(62 reference statements)
4
79
0
Order By: Relevance
“…The gas permeabilities decrease in the order: H 2 >CO 2 >O 2 >N 2 >CH 4 which follows the order of kinetic diameters of the gases. A similar sequence was also reported for PIM-EA-TB, KAUST-PI-1 and 6FDA-DAT, which all contain bridged-bicyclic moieties with the same kink angles [59,60].…”
Section: A C C E P T E Dmentioning
confidence: 74%
“…The gas permeabilities decrease in the order: H 2 >CO 2 >O 2 >N 2 >CH 4 which follows the order of kinetic diameters of the gases. A similar sequence was also reported for PIM-EA-TB, KAUST-PI-1 and 6FDA-DAT, which all contain bridged-bicyclic moieties with the same kink angles [59,60].…”
Section: A C C E P T E Dmentioning
confidence: 74%
“…Recently, Carta et al reported a new class of extremely rigid PIMs containing bridged non-planar bicyclic ring systems formed by a Troٛ ger's base (TB) polymerization reaction [14,[25][26][27][28][29][30]. The higher chain rigidity derived from the ethanoanthracene (EA) ring system combined with the TB unit led to membranes with high gas permeability and selectivity due to the larger interchain spacing and high fractional free volume (FFV) [15].…”
Section: A Polymer Of Intrinsic Microporosity (Pim) Is a Term Coined mentioning
confidence: 98%
“…PIMs [23,24] provide a new generation of highly rigid microporous materials with (i) excellent processability, (ii) highly rigid pore structures in which guest catalyst molecules can be readily embedded, (iii) good access of solvent and substrate to the catalyst through rigid pores and (iv) robustness towards corrosion. In our previous work, the poly-amine structure PIM-EA-TB [25] (synthesised based on a Tröger's base reaction [26][27][28]) has been employed to electrochemically grow palladium lamellae [29], to act as a host for molecular Fe(II)-porphyrinato electrocatalyst [30] and to protect gold nanoparticles [31] and fuel cell catalysts [32]. Recently, we have demonstrated proof of concept for the immobilisation of the molecular electrocatalyst 4-benzoyloxy-TEMPO (or 4B-TEMPO) into a porous PIM-EA-TB host film for the electrocatalytic oxidation of saccharides [33].…”
Section: Introductionmentioning
confidence: 99%